Surface ozone trend in major rice growing areas in Malaysia - Marzuki Ismail,; Azrin Suroto,; Nurul Ain Ismail,; Mohd Talib Latif, (Universiti Kebangsaan Malaysia, 2014)
Surface ozone or tropospheric ozone has been recognized as one of the major factors that can give adverse impact on crops including rice plants. Effects of ozone on rice plants could be seen in decreased of biochemical activities and physiological performance which contribute to yield reduction. In Malaysia, surface ozone is on the rise due to increment anthropogenic sources i.e. urbanization, transportation and also industrialization process. This condition is alarming due to the facts that rice is the major staple food to the majority of Malaysian population. In this study, exceedence of ozone exposure above an hourly threshold concentration of 40 ppb (AOT40) and ozone trends in four major rice growing areas in Malaysia were assessed using time series analysis of ozone data recorded in each area from January 2000 until December 2010 with a total of 132 readings. The results showed a steady increase in exceedence ozone of yearly AOT40 and statistical significant upward trend for ozone concentrations in each rice growing area in Malaysia. This finding was particularly alarming because ozone is able to inhibit production of rice yields. Preventive actions need to be implemented as soon as possible in order to alleviate ozone threat to our national food security agenda.